Novel MKRN3 gene mutation associated with central precocious puberty in a Chinese child: a case report - Wang, Jingna; Li, Rongmin; Wang, Jieying; Wu, Di; Lei, Shuqin; Sang, Yanmei; Chang, Jie (Frontiers in Endocrinology, 2024)
Objective: The objective of this study is to investigate the clinical presentation and underlying genetic etiology of a Chinese child diagnosed with idiopathic central precocious puberty (ICPP). Methods: Clinical data from a pediatric patient with ICPP, including medical history, physical examination findings, laboratory results, and imaging studies, were collected and analyzed. Whole exome sequencing (WES) was performed to identify potential pathogenic genetic variants underlying the patient's ICPP. Results: A 4-year and 9-month-old female patient presented with precocious puberty, characterized by accelerated growth, Tanner stage II breast development, and Tanner stage I pubic hair. A café-au-lait macule was observed on the patient's right flank. WES revealed a novel heterozygous frameshift mutation caused by a single nucleotide deletion (c.1219delA) in exon 1 of the makorin RING finger protein 3 (MKRN3) gene, resulting in a substitution of arginine (R) with glycine (G) at codon 407 (p.R407G). This frameshift mutation (p.R407Gfs*75), which was inherited from the patient's asymptomatic father, results in premature termination of its translation, leading to a truncated protein 73 amino acids downstream from the mutation site. Conclusion: This case underscores the genetic heterogeneity of ICPP and further implicates MKRN3 gene mutations in its pathogenesis. The identification of this novel pathogenic variant expands the known mutational spectrum associated with ICPP, particularly within the Chinese pediatric population. Comprehensive genetic testing should be considered in pediatric patients presenting with early-onset ICPP to facilitate accurate diagnosis, inform genetic counseling, and guide personalized management strategies.